Educação sexual emancipatória e os desafios contemporâneos: um ensaio teórico sobre o relatório das ofensivas antigênero - Donzeli, Taina Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This dissertation aims to investigate how anti-gender offensives impact the development and practice of emancipatory sex education in contemporary times. It is based on the report "Anti Gender-Offensives in Brazil: State policies, legislation and social mobilization" (2021). This document, prepared by several civil society organizations, took stock of the anti-gender offensives in Brazil between 2019 and 2021. It addresses the importance of emancipatory sex education as a tool to promote gender equality, respect for diversity, and the breaking of stigma and prejudice. In this research, the strategies of censorship and exclusion were analyzed, as well as the influence of neoconservatism on the development of public policies. We also examined the consequences of anti-gender offensives for guaranteeing the rights of women and LGBTQIAPN+ groups. The objective of this research was to analyze the impacts of anti-gender offensives on the possibility of promoting an emancipatory sexual education. In the methodology adopted, through categorization, it was sought to delimit and discuss how the offensive anti-gender influence in three specific areas: restriction of critical training of students, perpetuation of discrimination and exclusion, censorship of debates about gender and sexuality contributing to disinformation.

Esta dissertação se propõe a investigar de que modo as ofensivas antigênero repercutem no desenvolvimento e na prática da educação sexual emancipatória na contemporaneidade, tendo como base o Relatório “Ofensivas antigênero no Brasil: políticas de Estado, legislação e mobilização social” (2021). Esse documento, elaborado por diversas organizações da sociedade civil, fez um balanço das ofensivas antigênero no Brasil entre 2019 e 2021. Ele aborda a importância da educação sexual emancipatória como ferramenta para promover a igualdade de gênero, o respeito à diversidade, a quebra de estigmas e preconceitos. Nesta pesquisa, foram analisadas as estratégias de censura e exclusão, bem como a influência do neoconservadorismo no desenvolvimento das políticas públicas. Examinou-se também as implicações dessas ofensivas para a garantia dos direitos de mulheres e de grupos LGBTQIAPN+. O objetivo foi analisar os impactos das ofensivas antigênero na possibilidade de promoção de uma educação sexual emancipatória. Na metodologia utilizada, através da categorização, buscou-se delimitar e discutir o modo como as ofensivas antigênero influenciam em três áreas especificas: restrição à formação crítica dos estudantes, perpetuação da discriminação e da exclusão, censura de debates sobre gênero e sexualidade contribuindo para a desinformação.
Emancipatory sex education and contemporary challenges: a theoretical essay on the report of anti-gender offensives
Keywords: Educação sexual emancipatória; Offensive anti-gender; Emancipatory sex education; Emancipatory sex education